Effects of an Armillaria mellea Polysaccharide on Learning and Memory of D-Galactose-Induced Aging Mice - Li, Hongyu; Xu, Guangyu; Yuan, Guangxin (Frontiers in Pharmacology, 2022)
Armillaria mellea has been found and used in East Asia for hundreds of years. In traditional medicine, Armillaria mellea has been reported to show various pharmacological effects. Studies have shown that Armillaria mellea polysaccharides exhibit anti-oxidant and anti-apoptotic activities. In this study, a water-soluble polysaccharide (AMP-N-a-1), with an average molecular weight of 17KD, was isolated and purified from the water extract of Armillaria mellea by DEAE-52, Sepharose CL-4B and Sephadex G-100 column chromatography. AMP-N-a-1 was mainly composed of Man (1.65%), Glca (1.64%), Rha (1.82%), Gala (2.49%), Glc (90.48%), Gal (0.89%), Xyl (0.42%) and Ara (0.61%). AMP-N-a-1 was used to study the effect on the learning and memory of mice and its underlying mechanisms. The results showed that AMP-N-a-1 could significantly increase the activities of CAT (Catalase) and SOD (Superoxide dismutase), and reduce the content of NO (Nitric oxide) in mouse brain tissue. Meanwhile, AMP-N-a-1 could reduce the contents of NE (Norepinephrine) and DA (Dopamine), but increase the content of 5-HT (5-hydroxytryptamine) in mouse brain tissue. In addition, the immunofluorescence experiment showed that AMP-N-a-1 could promote the proliferation of hippocampal dentate gyrus neurons. The above results indicate that AMP-N-a-1 can significantly improve the learning and memory of mice, and the mechanism may be that AMP-N-a-1 can participate in the regulation of learning and memory through a variety of ways.